Secondary Socialization Model In Effort to Prevent The Spread of Covid-19 for Residents of Rt 015 Rw 08 Palmeriam Matraman East Jakarta - Novida Irawan; Bintang Nurijadi; Nabila Salmin Al Jaedi (Peneliti.net, 2023)
Socialization activities carried out by the government during the Covid-19 Pandemic to convey information to the public up to the RT environment level. The socialization was carried out to increase the danger posed and prevent the spread of Covid-19. Socialization needs to be carried out in the RT which is the closest part to the residents so that the delivery of information in the socialization is easily conveyed. This study discusses the secondary socialization model an effort to prevent the spread of Covid-19 in the RT 015 RW 08 Palmeriam Matraman East Jakarta. The purpose of this study was to understand the secondary socialization model used by RT administrators in delivering socialization. This study was analyzed through a secondary socialization model. The research used is qualitative with in-depth interviews, observation, and documentation as a source of data collection. The results showed that RT 015 RW 08 Palmeriam Matraman East Jakarta conducted socialization using a secondary socialization model. Socialization is done directly through individuals to the public. So that through secondary socialization it can help provide an understanding of the dangers and prevention of the spread of Covid-19